A meta-analysis of potential biomarkers associated with severity of coronavirus disease 2019 (COVID-19) - Celestin Danwang; Francky Teddy Endomba; Jan René Nkeck; Dominic Leandry Angong Wouna; Annie Robert; Jean Jacques Noubiap (BMC, 2020)
Abstract Background Prognostic factors for the Coronavirus disease 2019 (COVID1-9) are not well established. This study aimed to summarize the available data on the association between the severity of COVID-19 and common hematological, inflammatory and biochemical parameters. Methods EMBASE, MEDLINE, Web of sciences were searched to identify all published studies providing relevant data. Random-effects meta-analysis was used to pool effect sizes. Results The bibliographic search yielded 287 citations, 31 of which were finally retained. Meta-analysis of standardized mean difference (SMD) between severe and non-severe COVID-19 cases showed that CK-MB (SMD = 0.68,95%CI: 0.48;0.87; P-value:< 0.001), troponin I (SMD = 0.71, 95%CI:0.42;1.00; P-value:< 0.001), D-dimer (SMD = 0.54,95%CI:0.31;0.77; P-value:< 0.001), prothrombin time (SMD = 0.48, 95%CI:0.23;0.73; P-value: < 0.001), procalcitonin (SMD = 0.72, 95%CI: 0.34;1,11; P-value:< 0.001), interleukin-6 (SMD = 0.93, 95%CI: 0.25;1.61;P-value: 0.007),C-reactive protein (CRP) (SMD = 1.34, 95%CI:0.83;1.86; P-value:< 0.001), ALAT (SMD = 0.53, 95%CI: 0.34;0,71; P-value:< 0.001), ASAT (SMD = 0.96, 95%CI: 0.58;1.34; P-value: < 0.001), LDH (SMD = 1.36, 95%CI: 0.75;1.98; P-value:< 0.001), CK (SMD = 0.48, 95%CI: 0.10;0.87; P-value:0.01), total bilirubin (SMD = 0.32, 95%CI: 0.18;0.47;P-value: < 0.001), γ-GT (SMD = 1.03, 95%CI: 0.83;1.22; P-value: < 0.001), myoglobin (SMD = 1.14, 95%CI: 0.81;1.47; P-value:< 0.001), blood urea nitrogen (SMD = 0.32, 95%CI: 0.18;0.47;P-value:< 0.001) and Creatininemia (SMD = 0.18, 95%CI: 0.01;0.35; P-value:0.04) were significantly more elevated in severe cases, in opposition to lymphocyte count (SMD = -0.57, 95%CI:-0.71; − 0.42; P-value: < 0.001) and proportion of lymphocytes (SMD = -0.81, 95%CI: − 1.12; − 0.49; P-value:< 0.001) which were found to be significantly lower in severe patients with other biomarker such as thrombocytes (SMD = -0.26, 95%CI: − 0.48; − 0.04; P-value:0.02), eosinophils (SMD = − 0.28, 95%CI:-0.50; − 0.06; P-value:0.01), haemoglobin (SMD = -0.20, 95%CI: − 0.37,-0.03; P-value:0.02), albuminemia (SMD-1.67,95%CI -2.40; − 0.94; P-value:< 0.001), which were also lower. Furthermore, severe COVID-19 cases had a higher risk to have lymphopenia (RR =1.66, 95%CI: 1.26;2.20; P-value:0.002), thrombocytopenia (RR = 1.86, 95%CI: 1.59;2.17; P-value: < 0.001), elevated procalcitonin level (RR = 2.94, 95%CI: 2.09-4.15; P-value:< 0.001), CRP (RR =1.41,95%CI: 1.17-1.70; P-value:0.003), ASAT(RR =2.27, 95%CI: 1.76;2.94; P-value:< 0.001), CK(RR = 2.61, 95%CI: 1.35;5.05; P-value: 0.01), Creatininemia (RR = 3.66, 95%CI: 1.53;8.81; P-value: 0.02) and LDH blood level (RR = 2.03, 95%CI: 1.42;290; P-value: 0.003). Conclusion Some inflammatory (procalcitonin, CRP), haematologic (lymphocyte, Thrombocytes), and biochemical (CK-MB, Troponin I, D-dimer, ASAT, ALAT, LDH, γ-GT) biomarkers are significantly associated with severe COVID-19. These biomarkers might help in prognostic risk stratification of patients with COVID-19.